SMARTWALL: A NEW WEB-BASED PLATFORM FOR THE VALORIZATION OF THE MEDIEVAL WALL OF AVILA - L. J. Sánchez-Aparicio; R. Moreno-Blanco; J. A. Martín-Jiménez; P. Rodríguez-Gonzálvez; A. L. Muñoz-Nieto; D. González-Aguilera (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
As stated the Nara Document on Authenticity and the last Restoration Charter, valorisation of Cultural Heritage sites requires to understand its tangible and intangible values. These values need to be considered as variables that change along the time and space, and they are the result of the interaction between the cultural heritage assets with its history (civilization, societies, etc.). Under this basis, the research project SmartWall attempts to develop a new platform for the valorisation of the Medieval Wall of Ávila, and thus the transmission of its tangible and intangible values to the society. To this end, SmartWall uses an efficient combination between 360 images, 3D/4D models and a geospatial database. This combination provides the following capabilities: i) upgrading the information in real-time, adding, modifying or deleting any type of document; ii) filtering the information in accordance with specific criteria and; iii) managing the information according with different profiles of the user (e.g. expert user, students and tourists). All this information is boosted with a direct link to a 4D model of the Wall, which allows analysing any aspect of the Wall through time. The development and validation of the SmartWall platform was performed in the Alcázar Gate, one of the most emblematic parts of the Medieval Wall of Avila.